Repeat Storm Surge Disasters of Typhoon Haiyan and Its 1897 Predecessor in the Philippines - Soria, Janneli Lea Acierto (2017)
On 8 November 2013, Typhoon Haiyan impacted the Philippines with estimated winds of approximately 314 km h-1 and an associated 5–7-m-high storm surge that struck Tacloban City and the surrounding coast of the shallow, funnel-shaped San Pedro Bay. Typhoon Haiyan killed more than 6,000 people, superseding Tropical Storm Thelma of November 1991 as the deadliest typhoon in the Philippines. Globally, it was the deadliest tropical cyclone since Nargis hit Myanmar in 2008. Here, we use field measurements, eyewitness accounts, and video recordings to corroborate numerical simulations and to characterize the extremely high velocity flooding caused by the Typhoon Haiyan storm surge in both San Pedro Bay and on the more open Pacific Ocean coast. We then compare the surge heights from Typhoon Haiyan with historical records of an unnamed typhoon that took a similar path of destruction in October 1897 (Ty 1897) but which was less intense, smaller, and moved more slowly. The Haiyan surge was about twice the height of the 1897 event in San Pedro Bay, but the two storm surges had similar heights on the open Pacific coast. Until stronger prehistoric events are explored, these two storm surges serve as worst-case scenarios for this region. This study highlights that rare but disastrous events should be carefully evaluated in the context of enhancing community-based disaster risk awareness, planning, and response.